The sites of memory in the city of Madrid - Escalante, Lucía Soledad (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2021)
The proposed research inquired into the existent ties between the right to memory and the right to the city. For this purpose, those rights were analyzed from a critical theory of human rights and having, as a point of contact between both rights, the spatial inscriptions that materialize the collective memory in the city of Madrid. The investigation sought if those sites that materialize and guarantee memory could also guarantee the access to the right to the city. The methodology used consisted of a critical analysis of texts, an exhaustive survey and study of national and international norms and standards, local public policies, observation and registration of said sites and, finally, an in-depth interview using the case sample technique which is extremely important to the analyzed problem.